Influence of toilet access on antiretroviral adherence intention among pregnant and breastfeeding women who are HIV-positive and enrolled in Option B+. Issue 3 (4th March 2021) - Nutor, Jerry John; Slaughter-Acey, Jaime C.; Marquez, Shannon P.; DiMaria-Ghalili, Rose Ann; Momplaisir, Florence; Jemmott, Loretta S.
Abstract: We investigated the influence of toilet access on intention to adhere to antiretroviral therapy (ART) among women who are HIV-positive and enrolled in Option B+. A convenience sample of 150 women residing in Lusaka (urban) and Sinazongwe (rural) Districts of Zambia were recruited. if they were seeking pre- or post-natal care and were enrolled in Option B+. Intention to adhere to ART was assessed using four questions based on the Theory of Planned Behavior; the median score was used to distinguish high intention from low intention. Descriptive statistics were used to characterize access to toilet facilities and ART adherence intention in the entire sample and by rural and urban districts in Zambia. There was no significant difference ( p = .19) between rural and urban women's access to a flush toilet. After adjusting for toilet access, however, rural women were significantly less likely to be in the high adherence intention group (PR = 0.80, 95% CI 0.71-0.90, p < .001) but access to a flush toilet was associated with adherence intention (PR = 1.14, 95% CI (1.00 − 1.30). Community-led total sanitation in Zambia could increase ART adherence intention.